Effects of Surgical Side and Site on Mood and Behavior Outcome in Children with Pharmacoresistant Epilepsy - Andresen, Elizabeth N.; Ramirez, Maya; Kim, Kevin H.; Dorfman, Ava B.; Haut, Jennifer; Klaas, Patricia; Jehi, Lara; Shea, Katherine; Bingaman, William; Busch, Robyn M. (Frontiers in Neurology, 2014)
Children with epilepsy have a high rate of mood and behavior problems yet few studies consider the emotional and behavioral impact of surgery. No study to date has been sufficiently powered to investigate effects of both side (left/right) and site (temporal/frontal) of surgery. One hundred patients (aged 6-16) and their families completed measures of depression, anxiety and behavioral function as part of neuropsychological evaluations before and after surgery for pharmacoresistant epilepsy. Among children who had left-sided surgeries (frontal=16; temporal=38), there were significant interactions between time (pre to postoperative neuropsychological assessment) and resection site (frontal/temporal) on Anhedonia, Social Anxiety, and Withdrawn/Depressed scales. Patients with frontal lobe epilepsy (FLE) endorsed greater presurgical anhedonia and social anxiety than patients with temporal lobe epilepsy (TLE), with scores normalizing following surgery. While scores on the Withdrawn/Depressed scale were similar between groups before surgery, the FLE group showed greater symptom improvement after surgery. In children who underwent right-sided surgeries (FLE=20; TLE=26) main effects of time (patients in both groups improved) and resection site (caregivers of FLE patients endorsed greater symptoms than those with TLE) were observed primarily on behavior scales. Individual data revealed that a greater proportion of children with left FLE demonstrated clinically significant improvements in Anhedonia, Social Anxiety, and Aggressive Behavior than children with TLE. This is the first study to demonstrate differential effects of both side and site of surgery in children with epilepsy at group and individual levels. Results suggest that children with FLE have greater emotional and behavioral dysfunction before surgery, but show marked improvement after surgery. Overall, most children had good emotional and behavioral outcomes, with most scores remaining stable or improving.